Hebrew language assessment measure for preschool children: A comparison between typically developing children and children with specific language impairment. (January 2014) - Katzenberger, Irit; Meilijson, Sara
The Katzenberger Hebrew Language Assessment for Preschool Children (henceforth: the KHLA) is the first comprehensive, standardized language assessment tool developed in Hebrew specifically for older preschoolers (4;0–5;11 years). The KHLA is a norm-referenced, Hebrew specific assessment, based on well-established psycholinguistic principles, as well as on the established knowledge in the field of normal language development in the preschool years. The main goal of the study is to evaluate the KHLA as a tool for identification of language-impaired Hebrew-speaking preschoolers and to find out whether the test distinguishes between typically developing (TDL) and language-impaired children. The aim of the application of the KHLA is to characterize the language skills of Hebrew-speaking children with specific language impairment (SLI). The tasks comprised in the assessment are considered in the literature to be the sensitive areas of language skills appropriate for assessing children with SLI. Participants included 454 (383 TDL and 71 SLI) mid–high SES, monolingual native speakers of Hebrew, aged 4;0–5;11 years. The assessment included six subtests (with a total of 171 items): Auditory Processing, Lexicon, Grammar, Phonological Awareness, Semantic Categorization, and Narration of Picture Series. The study focuses on the psychometric aspect of the test. The KHLA was found useful for distinguishing between TDL and SLI when the identification is based on the total Z-score or at least two of the subtest-specific Z-scores in −1.25 SD cutoff points. The results provide a ranking order for assessment: Grammar, Auditory Processing, Semantic Categorization, Narration of Picture Series/Lexicon, and Phonological Awareness. The main clinical implications of this study are to consider the optimal cutoff point of −1.25 SD for diagnosis of SLI children and to apply the entire test for assessment. In cases when the clinician may decide to assess only two or three subtests, it is recommended that the ranking order be applied as described in the study.